THE URGENCY OF IMPLEMENTATION OF MULTICULTURAL EDUCATION IN SCHOOL IN ISLAMIC EDUCATION PERSPECTIVE (URGENSI IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DI SEKOLAH DALAM PERSPEKTIF PENDIDIKAN ISLAM) - Kurnaengsih Kurnaengsih (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2019)
This article aims to explore the urgency of implementation of multicultural education in school in perspective of islamic education. Indonesia simply can be called the multicultural society. Multicultural education is a process of cultivating a way of life to respects, sincere, and tolerant to cultures diversities that live in the midst of a pluralistic society. The implementation of multicultural education does not have to change the curriculum. Multicultural education lessons can be integrated into other subjects. It's just that guidance is needed for teachers to implement it. Multicultural education is expected to be the best solution in handling the diversity that exists, be it culture, religion, ethnicity, and so on by cultivating a spirit of respect for different things. Artikel ini bertujuan untuk mengeksplorasi urgensi implementasi pendidikan multikultural di sekolah dalam perspektif pendidikan Islam. Indonesia secara sederhana dapat disebut sebagai masyarakat multikultural. Pendidikan multikultural merupakan proses penanaman cara hidup menghormati, tulus dan toleran terhadap keragaman budaya yang hidup di tengah-tengah masyarakat plural. Adapun pelaksanaan pendidikan multikultural tidaklah harus merubah kurikulum. Pelajaran pendidikan multikultural dapat terintegrasi pada mata pelajaran lainnya. Hanya saja diperlukan pedoman bagi guru untuk menerapkannya. Pendidikan multikultural diharapkan mampu menjadi solusi terbaik dalam menangani keragaman yang ada, baik itu budaya, agama, etnis, dan sebagainya dengan cara menumbuhkan semangat penghargaan terhadap hal yang berbeda.